2015
DOI: 10.1016/j.jcot.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of functional outcome and complications of locking calcaneum plate for fracture calcaneum

Abstract: Locking calcaneal plate a b s t r a c t Background: Open reduction and internal fixation (ORIF) is the treatment of choice for displaced intra-articular calcaneal fracture at many orthopaedic trauma centres. In this prospective study, we evaluated the functional outcome and complications of locking compressive calcaneum plate for displaced intra-articular fracture calcaneum.Methods: Between October 2011 and March 2012, 30 patients with displaced intra-articular fracture calcaneum attending the outdoor and emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Calcaneal fractures are one of the most frequently encountered fractures of the hindfoot [ 1 , 2 ] and have been estimated to account for approximately 1% to 2% of all fractures. [ 3 ] High-energy trauma is the main cause and often results in displaced intra-articular calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Calcaneal fractures are one of the most frequently encountered fractures of the hindfoot [ 1 , 2 ] and have been estimated to account for approximately 1% to 2% of all fractures. [ 3 ] High-energy trauma is the main cause and often results in displaced intra-articular calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…This fact was also noted by other authors. 17 In this study found significant correlation between the type of fracture and post-operative Bohler's angle. Patient having post-operative Bohler's angle <20⁰ were more in sanders type IV as compared to type II and III (Table 4).…”
Section: Discussionmentioning
confidence: 50%
“…Patient having post-operative Bohler's angle <20⁰ were more in sanders type IV as compared to type II and III (Table 4). 17 A previous study by Longino et al reported no significant difference between post-operative radiological and clinical results of locking calcaneum plate osteosynthesis with and without bone grafting, thus bone grafting was omitted from our study. 18…”
Section: Discussionmentioning
confidence: 88%
“…Surgical treatment with open reduction and internal synthesis (ORIF) [6] is considered the standard treatment for CF, but it is associated with many complications, particularly in patients with systemic diseases, such as diabetes and peripheral vascular disease. erefore, several minimally invasive techniques have been proposed to avoid the frequent and recurrent postoperative problems related to these fractures, to ensure good reduction with fewer complications and to reduce preoperative and hospitalization times; these techniques include arthroscopically assisted reduction and fixation, external fixation, balloon calcaneoplasty [7,8].…”
Section: Introductionmentioning
confidence: 99%